P2A Work Program to Enhance Women's Understanding of Wiritan on the Concept of Ghibah - Adinda Rizki Julianti; Winda Kustiawan (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study examines the work program of the Religious Practice Supervisor (P2A) in Tambusai Batang Dui Village, Mandau District, Bengkalis Regency to improve the understanding of women's wiritan about gossip. Ghibah is talk about others that can be detrimental, often occurs in social interactions, especially among mothers. Therefore, a good understanding of ghibah is very important to build healthy social relationships. The data collected in this study were collected through observation and in-depth interviews. In addition, there are positive changes in their social behavior, where mothers are more careful in talking about others. The conclusion of this study is that the P2A work program in improving the understanding of ghibah among women's wiritan in Tambusai Batang Dui Village they create a program of religious teaching classes and studies, there are also several challenges and obstacles such as the lack of participation from women's wiritan and the lack of literacy and understanding of ghibah among women's wiritan. This study recommends the need for further programs to deepen understanding of communication ethics and build awareness of the importance of maintaining harmony in social interactions.